Motor Planning under Unpredictable Reward: Modulations of Movement Vigor and Primate Striatum Activity - Opris, Ioan; Lebedev, Mikhail; Nelson, Randall J. (Frontiers in Neuroscience, 2011)
Although reward probability is an important factor that shapes animal behavior, it is not well understood however, how the primate brain translates reward expectation into the vigor of movement (reaction time and speed). To address this question, we trained two monkeys in a reaction time task that required wrist movements in response to vibrotactile and visual stimuli, with a variable reward schedule. Correct performance was rewarded in 75 % of the trials. Monkeys were certain that they would be rewarded only in the trials immediately following withheld rewards. In these trials, the animals responded sooner and moved faster. Single-unit recordings from the dorsal striatum revealed that modulations in striatal neurons reflected such modulations of movement vigor. First, in the trials with certain rewards, striatal neurons modulated their firing rates earlier. Second, magnitudes of changes in neuronal firing rates depended on whether or not monkeys were certain about the reward. Third, these modulations depended on the sensory modality of the cue (visual vs. vibratory) and/or movement direction (flexions vs. extensions). We conclude that dorsal striatum may be a part of the mechanism responsible for the modulation of movement vigor in response to changes of reward predictability.